DEMENTIA ACROSS LOCAL DISTRICTS IN ENGLAND 2014–2015. (11th November 2018) - Pendleton, N; Tambupolon, G; Nazroo, J; Maharani, A
Abstract: Although the rates of dementia have been shown to be declining in England and US, the number of older people needing dementia care is projected to rise rapidly, putting tremendous pressure on services. We analysed dementia prevalence (ascertained using the Telephone Interview for Cognitive Status (TICS) in people aged >60 living in England, drawing data from the English Longitudinal Study of Ageing 2014–2015. Data were further matched with local districts statistics and analysed using a multilevel logistic model. A number of individual risk factors were considered including social determinants, internet use, social connections and health behaviours. This was then co-analysed with two contextual factors: the index of multiple deprivation and land use mix. We will show the variation in maps of dementia prevalence across districts in England, and model the effect of individual factors and area characteristics in predicting dementia prevalence..